Cumulative Dispensing of Oral Corticosteroids Over 12 Months in People with COPD - Burge AT; Cox NS; Dal Corso S; Jones AW; Faqih FM; Holland AE (International Journal of COPD)
Angela T Burge,1,2 Narelle S Cox,1,3 Simone Dal Corso,1 Arwel W Jones,1 Fahrayhansyah Muhammad Faqih,1 Anne E Holland1– 4 1School of Translational Medicine, Monash University, Melbourne, VIC, Australia; 2Department of Physiotherapy, Alfred Health, Melbourne, VIC, Australia; 3Institute for Breathing and Sleep, Melbourne, VIC, Australia; 4Department of Respiratory Medicine, Alfred Health, Melbourne, VIC, AustraliaCorrespondence: Angela T Burge, Respiratory Research@Alfred, Monash University, Level 6 The Alfred Centre, 99 Commercial Road, Melbourne, VIC, 3004, Australia, Email angela.burge@monash.eduPurpose: Oral corticosteroids (OCS) are recommended for the treatment of exacerbations in people with COPD; however, high cumulative lifetime doses (≥ 1000mg prednisolone-equivalent) are associated with adverse health effects. This issue is well defined in asthma but is less well understood in COPD. The aim of this study was to examine cumulative OCS dispensed to people with COPD over 12 months.Patients and Methods: This was a secondary analysis of data from two randomised controlled trials involving people with COPD followed up for 12 months following pulmonary rehabilitation. Clinical and administrative (respiratory-related hospital admissions and emergency presentations, dispensed OCS and COPD maintenance medications) data were examined to determine cumulative OCS dose relative to the 1000mg threshold and the relationship with clinical features.Results: Of 232 participants (126 females, age mean 68 ± SD 9 years, FEV1 53 ± 22% predicted), 48% (n = 112) were dispensed OCS at least once over 12 months. Sixty-two participants (26%) were dispensed ≥ 1000mg. Participants with a high cumulative dose were more likely to have had a respiratory admission (OR 4.1, 95% CI 2.3 to 8.7) and greater breathlessness (modified Medical Research Council scale ≥ 2, OR 2.5, 95% CI 1.3 to 5.0); no relationship with disease severity or maintenance medications was demonstrated.Conclusion: One in four people with COPD were dispensed unsafe lifetime cumulative OCS doses over a period of only 12 months. Further work is needed to determine the magnitude of this issue in COPD and strategies to address exposure to high doses of OCS.Keywords: exacerbations, systemic corticosteroids, prescriptions, side effects